Seroprevalence of leptospira interrogans serovar djasiman in quarantined pigs - Modolo, J. R. [UNESP] (2000)
Leptospirosis is a worldwide zoonosis affecting all mammals, including pigs and cattle. Pigs are considered one of the most important domestic animals, whcih can carry leptospies. On infection, they show a long lasting and abundant leptospiruria, not only maintaining the endemic disease in swine farms, but also remaining as sources of infection for man and other animals (Palit et al., 1988 ; Bolt and Marshall, 1995). Affected animals show clinical signs, such as abortion, sterility, death at birth, birth of weaklings besides heavy mortality, causing great economic losses (Palit et al., loc. cit.). For transmission of the disease, rodents, including wild rodents, play an important role. These animals are natural carriers of the leptospires and an important source of infection for domestic animals (Correa and Correa, 1992; Zamora et al., 1995). This paper reports the presence of specific antibodies for L. interrogans serovar djasiman in quarantined pigs.